ANALISIS PENERAPAN SISTEM PEMBAYARAN CASH ON DELIVERY (COD) UNTUK MENINGKATKAN PENJUALAN BISNIS ONLINE PADA APLIKASI MARKETPLACE TOKO DEALS OF THE DAY - Athellya Hasan; TS Reza TS Reza (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This research was conducted to find out how the application of the Cash On Delivery (COD) payment system to increase the sales’ Deals Of The Day stores and anu obstacles from the implementation of the Cash On Delivery (COD) payment system.The research method use in this study is a qualitative research method. Data collection techniques used was interviews and observations. The data analysis technique used is qualitative descriptive analysis, namely data collection from various sources is presented to describe all research objects based on the facts in the field related to the implementation of the Cash On Delivery (COD) payment system to increases sales and the constraints of the payment system.From the result of data processing shows the application of the Cash On Delivery (COD) payment system to increase the sales’ Deals Of The Day store is appropriate even though there are some obstacles but it does not reduce the benefits obtaiined